Cancer in indigenous people in Latin America and the Caribbean: a review. (3rd December 2013) - Moore, Suzanne P.; Forman, David; Piñeros, Marion; Fernández, Sdenka M.; de, Marceli; Bray, Freddie
Abstract Cancer is a leading cause of death in Latin America but there have been few assessments of the cancer burden for the 10% of the population who are indigenous. Evidence from other world regions suggests cancer survival is poorer for indigenous people than for others due to a greater incidence of case‐fatal cancers, later stage at diagnosis, and less cancer treatment. A status report on the cancer profile of indigenous people in Latin America and the Caribbean (LAC) is therefore clearly warranted. We undertook a systematic review of the peer‐reviewed literature in academic databases, and considered evidence from cancer registries from 1980, to assess cancer epidemiology among indigenous people in LAC. We identified 35 peer‐reviewed articles pertaining to cancer in indigenous people. Rates of cervical cancer in parts of Brazil, Ecuador, and Guyana, stomach cancer rates in regions of Chile and gallbladder rates in Chile and Bolivia, were higher for indigenous compared to others. Breast cancer rates were lower in Ecuador, Brazil, and Chile. Six cancer registries in Brazil provided incidence data but no other reports of incidence, mortality, or survival were identified. There was a paucity of data surrounding the cancer burden of indigenous people in LAC. In view of predicted increases in cancer rates in ensuing decades, and the disparities in burden already experienced by indigenous people in the region, it is imperative that cancer profiles are obtained and cancer control measures identified and prioritized.